Grenada : Ex Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Ex Post Assessment of Longer-Term Program Engagement on Grenada. Grenada's engagement with the IMF played an important role in supporting the small island economy after it was buffeted by major adverse shocks. IMF support catalyzed substantial donor aid in the wake of unprecedented damage from two hurricanes and provided additional resources when the global crisis hit. Key reforms were also advanced, including the implementation of a value-added tax and strengthening of the nonbank regulatory framework. Executive Directors have agreed that a new program should support urgently needed fiscal consolidation, promote faster and more inclusive growth, and focus on a few macro-critical reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet